Maltese primary school teachers' developing understanding of effective use of ICT in classrooms through an enquiry group process - Gialanze, Michelle (2011)
The context of this research was the European Union (EU) funded Specialised Animated Interactive Learning (S.A.I.L.) project that set out to incorporate group work as well as to integrate information computer technology (ICT) within primary school classrooms in three European countries. As part of this project, online resource material on the Romany culture was developed and introduced to a group of primary school teachers in Malta. A self-selected group of five of these teachers formed a collaborative enquiry group. The focus of the research was the teachers’ developing classroom practice and pedagogic understanding as evidenced by their developing use of pedagogic language and observations of classroom practice.